2019
DOI: 10.1016/j.jrp.2019.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Old dog, new tricks: Age differences in dog personality traits, associations with human personality traits, and links to important outcomes

Abstract: The authors would like to thank M. Brent Donnellan (human), C. Emily Durbin (human), Ernie (Beagle), Harper Lee (Sheltie), Belle (Pitbull), Tasha (Cocker Spaniel), Misty (mixed), Sissy (mixed), Harley (Husky), Lola (mixed), and Bowlby (the cat) for their inspiration and comments on previous versions of this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 105 publications
5
30
1
Order By: Relevance
“…Additionally, as the owners were contacted through social media the sample may have been subject to selection bias, and as such it is not possible to determine whether the results are generalisable to the population. However, the age related results are similar to Chopik and Weaver's (43) study that used the same questionnaire in populations in the US, the questionnaire showed good reliability, and the questionnaire method has previously been proven to be reliable and valid (22) and (17). Many of the associations found can be used to generate new hypotheses and tests that will help to validate the results.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Additionally, as the owners were contacted through social media the sample may have been subject to selection bias, and as such it is not possible to determine whether the results are generalisable to the population. However, the age related results are similar to Chopik and Weaver's (43) study that used the same questionnaire in populations in the US, the questionnaire showed good reliability, and the questionnaire method has previously been proven to be reliable and valid (22) and (17). Many of the associations found can be used to generate new hypotheses and tests that will help to validate the results.…”
Section: Discussionsupporting
confidence: 75%
“…Sex effects have been reported in 38% of studies [reviewed in Gartner (13)], however, reports are often conflicting. In general, results show that males have higher aggression (31,34,43,44) and boldness (35,36) and lower sociability (36) than females. Conversely, female dogs have higher fearfulness (40,45), and lower dominance over dogs than males (14).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Questionnaires are known to be a less reliable, less objective method of assessment, although they are less time consuming to administer [19]. It may thus not be surprising to see differences between our results and those in literature, because all previous studies were done using questionnaires only [25,54,55], or even the same Big Five factor taxonomy in both dog and owner assessments [25], just to be able to easily compare dyad scores.…”
Section: Discussioncontrasting
confidence: 58%
“…In line with our results, Starling et al [ 25 ] also observed a decrease in boldness with increased age, however, their boldness factor was created from an owner questionnaire, and was comprised of more variables than our factor. One explanation for the reduction in boldness in older dogs could be that as dogs’ age and accumulate experiences, they engage less with their surroundings and show a reduction in excitement and/or curiosity, which may lead to behaviour that appears shier [ 24 ]. As such, they become less inclined to approach strangers or explore a new environment [ 25 ].…”
Section: Discussionmentioning
confidence: 99%